2019
DOI: 10.3389/fcimb.2019.00209
|View full text |Cite
|
Sign up to set email alerts
|

Featured Species-Specific Loops Are Found in the Crystal Structure of Mhp Eno, a Cell Surface Adhesin From Mycoplasma hyopneumoniae

Abstract: Enolase is an evolutionarily conserved enzyme involved in the processes of glycolysis and gluconeogenesis. Mycoplasma hyopneumoniae belongs to Mycoplasma , whose species are wall-less and among the smallest self-replicating bacteria, and is an important colonizing respiratory pathogen in the pig industry worldwide. Mycoplasma hyopneumoniae enolase ( Mhp Eno) expression is significantly increased after infection and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…For example, in S. suis serotype 2 enolase was suggested to be a potential virulence factor for CNS invasion as it induced IL-8 release [23]. Although enolase, an enzyme of the glycolytic pathway and prototypic moonlighting protein, has shown to act as adhesin on the cell surface of several mycoplasma species [26][27][28][29][30], its potential moonlighting activity in Mhr remains to be elucidated. Interestingly, enolase is also suggested to play a role in human tic disorders and to act as an autoantigen in Hashimoto's encephalopathy [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in S. suis serotype 2 enolase was suggested to be a potential virulence factor for CNS invasion as it induced IL-8 release [23]. Although enolase, an enzyme of the glycolytic pathway and prototypic moonlighting protein, has shown to act as adhesin on the cell surface of several mycoplasma species [26][27][28][29][30], its potential moonlighting activity in Mhr remains to be elucidated. Interestingly, enolase is also suggested to play a role in human tic disorders and to act as an autoantigen in Hashimoto's encephalopathy [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The insoluble secretome (or surfaceome) of M. hyopneumoniae also acts as a reservoir of virulence factors (Table 2), which strongly contribute to EP establishment. Proteomic studies focused on surface proteins have demonstrated that this cell fraction is enriched with adhesion proteins (discussed in section 4.1), lipoproteins, and proteases, among others [75,86]. The roles of these proteins in immunomodulation and cell damage are discussed in the following sections.…”
Section: Protein Secretion Of M Hyopneumoniae and Its Impact On Pathmentioning
confidence: 96%
“…A repertoire of at least 35 M. hyopneumoniae proteins have been previously associated with cell adhesion, including several related to the P97/P102 paralog families and other surface proteins that moonlight as adhesins [78,84,85] (Table 1). However, the number of M. hyopneumoniae adhesins can be higher, considering that its surfaceome includes more than 290 proteins [72,75,86] and that many uncharacterized surfacedisplayed proteins may bear adhesion properties. Moreover, M. hyopneumoniae pathogenic and nonpathogenic strains, and the nonpathogenic M. flocculare, which differ in pathogenicity and were classically described as having differential adhesion capacities [87], share almost their entire repertoires of known adhesins, according to more recent comparative genomics and proteomics studies [72,75,87], also pointing out to differences beyond the mere sets of known adhesins.…”
Section: Hyopneumoniae Adhesion Determinantsmentioning
confidence: 99%
“…Moreover, both MHJ_0125, a glutamyl aminopeptidase, and MHJ_0461, a leucine aminopeptidase, have moonlighting roles as adhesins on the surface of M. hyopneumoniae; MHJ_0461 also binds to foreign double-stranded DNA [51,52]. Eno in M. hyopneumoniae and M. suis also play crucial roles in adherence, invasion, and infections [53,54].…”
Section: Adhesins For Pathogenic Mycoplasmas In Swinementioning
confidence: 99%